Magnetic tracking using a modular C++ environment for image-guided interventions. Issue 4 (4th July 2022) - Cavaliere, Marco; Walsh, Conor; Jaeger, Herman Alexander; O'Donoghue, Kilian; Cantillon-Murphy, Pádraig
ABSTRACT: Magnetic tracking enables instrument tracking for image-guided interventions when no line of sight is available. This paper describes the first steps towards a more cost-effective, modular, and adaptable approach that builds upon prior work in open hardware architectures for magnetic tracking in image-guided interventions. An exemplary C++ framework is implemented and demonstrated with the open-hardware Anser EMT system. System performance in speed, accuracy, and precision of the C++ implementation is analysed. Static positioning accuracy and precision are calculated within the Region of Interest (ROI) and an average position error of 1.0 ± 0.1 mm is demonstrated. Results show an indicative increase in the update rate using the C++ framework and substantially lower memory requirements, compared to the previously optimised Python and Matlab solvers. These preliminary results provide the basis for future development which will integrate the C++ framework in a 3D Slicer module, greatly extending the adaptability of the platform for customisation in advanced image-guided procedures.